Inflation and Attention Thresholds - Korenok, Oleg; Munro, David; Chen, Jiayi (The Review of Economics and Statistics, 2026)
Abstract One of the dangers of high inflation is that it can cause individuals to pay close attention to it. This internalization of inflation can lead to an accelerationist regime, making inflation harder to control. We empirically assess the relationship between attention and inflation for 38 countries. Our measures of attention are constructed from Internet search behavior or the popularity of inflation mentions on Twitter. We find evidence that attention thresholds exist for most of the countries, and that they typically occur between 2% and 4% inflation. We also document interesting variability across countries and find similar thresholds in newspaper coverage of inflation.